1987
DOI: 10.1073/pnas.84.24.9194
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the cDNA encoding the Epstein-Barr virus/C3d receptor (complement receptor type 2) of human B lymphocytes.

Abstract: Complementary DNA clones for complement receptor type 2 (CR2), the B-lymphocyte membrane protein that serves as the receptor for Epstein-Barr virus and the C3d complement fragment, were obtained by screening a Xgtll library generated from Raji B lymphoblastoid cell mRNA. A 4.2-kilobase (kb) clone, representing the entire coding sequence of the protein plus untranslated 5' and 3' nucleotide sequences was obtained and sequenced. The 4.2-kb clone, which contains all but about 500 base pairs (bp) of the 5' untrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(74 citation statements)
references
References 37 publications
3
71
0
Order By: Relevance
“…CR2 also interacts with autoantibodies present in serum of polyarthritis rheumatoid patients (13) and with CD23 (14). Molecular cloning indicated that CR2 is constituted by a large extracellular domain of 954 aa composed of 15-16 short consensus repeats, a 24-aa transmembrane domain, and a 34-aa intracellular domain (15,16). CR2 allows C3d and EBV to induce proliferation (17,18) or transformation (8), respectively.…”
Section: Activation Of the Ebv/c3d Receptor (Cr2 Cd21) Onmentioning
confidence: 99%
“…CR2 also interacts with autoantibodies present in serum of polyarthritis rheumatoid patients (13) and with CD23 (14). Molecular cloning indicated that CR2 is constituted by a large extracellular domain of 954 aa composed of 15-16 short consensus repeats, a 24-aa transmembrane domain, and a 34-aa intracellular domain (15,16). CR2 allows C3d and EBV to induce proliferation (17,18) or transformation (8), respectively.…”
Section: Activation Of the Ebv/c3d Receptor (Cr2 Cd21) Onmentioning
confidence: 99%
“…CD21 is composed of an extracellular domain containing 15 or 16 repeating structural elements termed short consensus repeats (SCRs), a transmembrane region, and a 34-aa cytoplasmic domain (23,24). CD21 and CD35 (complement receptor 1) are alternative splice products of the same Cr2 gene in mice, but are encoded by different genes in humans (25,26).…”
Section: Cd21 Is Expressed On Fdcs and Mature B Cells With Expressiomentioning
confidence: 99%
“…Because delivery of the viral genome into the cell involves major rearrangements of the capsid structure, entry must be a tightly regulated process, which is triggered by the cell. The mechanism of entry can be, in the case of enveloped viruses, by fusion of the viral Paul et al, 1989;Choi et al, 1990Weis et al, 1988Fried et al, 1981Dalgleish et al, 1984Mendelsohn et al, 1989Greve et al, 1989Staunton et al, 1989;Tomassini et al, 1989Acharya et al, 1989Mason et al, 1993Moore et al, 1987Tanner et al, 1987 J.W. Kim et al, 1991;H.…”
mentioning
confidence: 99%